PENGETAHUAN KONSUMEN TERHADAP DAUN KELOR DAN PRODUK OLAHAN DAUN KELOR - Hidayat, Syarif Imam; Mubarokah, Mubarokah; Rosyardi, Nabila Rizkika Ramadhani (Agridevina : Berkala Ilmiah Agribisnis, 2024)
When the Covid-19 pandemic broke out in 2020, health became important for all humans, scientists from various parts of the world reported that moringa leaves had antiviral potential that was more effective against influenza viruses and had been proven in vitro tests, so moringa leaves became known again by the people of Indonesia and abroad as an alternative to herbal medicines and herbs to increase immunity. This study is devoted to consumers of moringa leaf processed products. The purpose of this study was to identify consumer knowledge of moringa leaves and processed products. The type of research used is qualitative phenomenology-based descriptive, which aims to obtain a comprehensive picture and understanding based on the results of individual experiences on the phenomena that occur. The Data were obtained using Accidental Sampling technique by determining the respondents by chance. Criteria respondents are customers who have purchased and ever consumed processed products moringa leaves. The number of respondents in this study is 30 people from consumers of processed moringa leaf products. Data from this study were obtained through observation, interviews, and questionnaires. The Data was processed using Miles and Huberman analysis. The results of this study indicate that not all consumers know about moringa leaves and moringa leaf processed products, so consumers choose, Buy, and consume their products based only on the assumption of reliability and health.